Peran Kejujuran dalam Meningkatkan Penyelesaian Konflik Interpersonal di Media Sosial - Lintang Dwi Aprilaa; Akbar Nicholas Saputra; Diandi Nur Hakim (CV. ITTC INDONESIA, 2023)
This paper covers the role of honesty in enhancing interpersonal conflict resolution on social media. Interpersonal conflict can happen to anyone, especially in social media. There are many ways to resolve interpersonal conflicts. One of them is practicing honesty. Why honesty? Because honesty is one of the requirements for building healthy and harmonious interpersonal communication. The purpose of this study is to explain how the role of honesty in improving interpersonal conflict resolution on social media. This study uses a quantitative approach, namely using a questionnaire, and the distribution of Google forms as data collection, with the object of all people using social media. which after the data is collected, uses an inductive mindset as a conclusion. From the data that has been collected, it can be concluded that honesty plays a very important role in improving interpersonal conflict resolution on social media. honesty will build mutual trust, prevent miscommunication and misunderstandings, strengthen relationships, build mutual respect, and encourage effective problem-solving.